Terror, etnicidad y la imagen del judío en el cine argentino contemporáneo - Tzvi Tal (Centre de Recherches sur les Mondes Américains, 2010)
The frequent representation of Jews and Jewish themes in contemporary Argentine cinema reflects the changes affecting society and culture as a result of neoliberal reforms introduced since the early nineties. Socio-economic and political changes, as well as multiculturalism and the consequences of the terrorist attack on the headquarters of the Jewish community in Buenos Aires, have displaced representations of Jewish ethnicity, previously marginal or repressed, toward the focus of the reconstruction of Argentinian identity in cinema.